Sources of nitrate in a heavily nitrogen pollution bay in Beibu Gulf, as identified using stable isotopes - Cai, Shangjun; Lao, Qibin; Jin, Guangzhe; Chen, Chunqing; Zhou, Xin; Zhu, Qingmei; Lu, Xuan (Frontiers in Marine Science, 2022)
Eutrophication, mainly caused by the oversupply of inorganic nitrogen and phosphate, has increased and become a serious environmental problem in the coastal bays of Beibu Gulf, a newly developing industry and port in South China. However, the sources of nitrate are poorly understood in the gulf. In this study, nitrate dual isotopes (δ15N-NO3- and δ18O-NO3-) and ammonium isotopes (δ15N-NH4+) were measured during the rainy season to identify the nitrate sources and elucidate their biogeochemical processes in Xi Bay, a semi-enclosed bay that is strongly affected by human activities in the Beibu Gulf. The results showed that a high dissolved inorganic nitrogen (DIN, 10.24-99.09 µmol L-1) was observed in Xi Bay, particularly in the bay mouth. The concentrations of DIN in the bay were 1.5 times higher than that in Qinzhou Bay and 1.7 times than that in Tieshangang Bay, which mainly influenced by the intensive human activities (i.e., industrial and port activities). In addition, lower values of δ15N-NO3- and δ18O-NO3- and higher values of δ15N-NH4+ were observed in the upper bay, suggesting that microbial nitrification occurs in the upper bay, which was the dominant nitrate source in the upper bay (39%). In addition to nitrification, external sources, including sewage and manure (33%), soil N (15%) and fertilizer (11%), contributed to the higher nutrients in the upper bay. In the lower bay, severe nitrogen pollution led to a weaker impact of biological processes on isotopic fractionation, although a high Chl a level (average of 7.47 µg L-1) was found in this region. The heavy nitrate pollution in the lower bay mainly originated from sewage and manure (54%), followed by soil N (26%) and fertilizer (17%). The contribution of the nitrate source from atmospheric deposition was relatively low in the bay (<3%). This study suggests that biogeochemical processes have little impact on nitrate dual isotopes under heavy nitrogen pollution, and isotopes are an ideal proxy for tracing nitrogen sources.